Risk Factors for Return to the Operating Room after Resident-Performed Cataract Surgery. (17th February 2018) - Menda, Shivali A.; Driver, Todd H.; Neiman, Alexandra E.; Blumberg, Seth; Naseri, Ayman; Stewart, Jay M.
ABSTRACT: Objective : Investigate risk factors for unplanned return to the operating room after resident-performed cataract surgery. Design: Retrospective case-control study. Setting: Institutional. Methods : Study population: All patients with reoperation within 90 days of resident-performed phacoemulsification were matched to four control eyes which had surgery within 30 days of the reoperation at the same institution. Observation Procedure: Billing codes were used to identify all patients who underwent resident-performed intended phacoemulsification with intraocular lens placement from January 2005 to December 2010. Main Outcome Measures: Investigated risk factors for reoperation included cataract characteristics and preexisting ocular co-morbidities, including diabetic retinopathy, retinal detachment history, glaucoma, corneal pathology, and uveitis. Additional preoperative risk factors studied included resident training year, history of tamsulosin use, phacodonesis, pupillary dilation, presence of pseudoexfoliation, myopia, history of trauma, visual acuity, and monocular status. Intraoperative variables were the use of iris expansion devices, use of capsular stain, attending type, incision type, use of sutures, vitreous loss, anesthesia type, and phacoemulsification technique. Results : There were 67 returns to the operating room (i.e., cases) over five years that were assigned to 268 control eyes. In preoperative multivariate analysis, phacoemulsification done by a first- or second-year resident (OR 3.2, 95% CI: 1.7–6.0, p < 0.001) was associated with an increased risk of reoperation. In postoperative multivariate analysis, only the use of the divide-and-conquer technique (OR 4.0, 95% CI:1.7–9.2, p = 0.001) was associated with an increased risk of reoperation. Conclusions : Phacoemulsification done by a junior resident or using the divide-and-conquer technique had the highest risk of reoperation.